2018
DOI: 10.1063/1.5042444
|View full text |Cite
|
Sign up to set email alerts
|

Telegraphic switching signals by magnet tunnel junctions for neural spiking signals with high information capacity

Abstract: Magnetic tunnel junctions (MTJs) operating in the superparamagnetic regime produce telegraphic signals that emulate neural spiking signals. Previous studies have characterized the random spiking signals produced by MTJs in terms of the percentage of time spent in the anti-parallel (AP) magnetization state (referred to as the “AP rate”) but ignore the switching rate of the MTJ. In this work, we demonstrate that with proper tuning of both an external bias field and a bias voltage, we can control the average dwel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Efforts have been put into developing a suitable hardware for accelerating evaluation of this function, many of which are OH based on magnetoresistive random access memory (MRAM) technology which is a major contender in the field of nonvolatile memory using stable magnets to store information in the form of 0's and 1's. By contrast, BSN's can be built out of nanomagnets designed to have low energy barriers [11]- [18]. The performance of such BSN designs are largely dependent on the magnetization fluctuation rates of the LBM's, making it important to design the low barrier magnet to have a high fluctuation rate.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been put into developing a suitable hardware for accelerating evaluation of this function, many of which are OH based on magnetoresistive random access memory (MRAM) technology which is a major contender in the field of nonvolatile memory using stable magnets to store information in the form of 0's and 1's. By contrast, BSN's can be built out of nanomagnets designed to have low energy barriers [11]- [18]. The performance of such BSN designs are largely dependent on the magnetization fluctuation rates of the LBM's, making it important to design the low barrier magnet to have a high fluctuation rate.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the magnitude of the external magnetic field and "write" current are independent control knobs that can be used to modulate the device lifetimes, τ P and τ AP , and hence the precise temporal code. Recent experiments on a CoFeB MTJ stack have demonstrated that such a control is indeed possible for a range of external fields and currents 23 . However, using an external tunable magnetic field to bias MTJ spiking neurons is not feasible from the scalability perspective for neuromorphic computing applications.…”
mentioning
confidence: 99%
“…One is that it can be used to generate stochastic switching signals in thermally stable MTJs as well as sMTJs [79]. Second is that the average switching rate of the signals generated can be tuned by over four orders of magnitude and reach switching rates above 1 MHz [79], [80], [81]. The third, and most unique, feature of dual biasing is that the two biases can control the AP-and P-state dwell times separately, which we refer to as two degrees of tunability, and implies that the average output and average switching rate can be tuned independently.…”
Section: Dual-biased Mtjs For Asynchronous Methodsmentioning
confidence: 99%